Detection and Correction of Style Errors Present in Punjabi Sentences - Sharma, SK (International Journal of Computer Sciences and Engineering, 2025)
Detection and correction of style errors in a language plays an important role in development of language related resources like Machine Translation, Grammar checking, Natural Language Interfaces etc. Style errors may include various types of errors like Missing sentence ender, Wrong sentence ender, Error due to missing comma, Repeated/duplicate word Error, error due to missing conjunction etc.. Though considerable work has been done in the area for English and related languages, but the Indian Language scenario presents a relatively more complex and uphill task. In this paper, author has presented an algorithm for detection of various style errors present in Punjabi language. Author tested his algorithm using three different kinds of data sets and it is observed that the algorithm performs better for wrong sentence ender and duplicate word type error as compare to missing conjunction type style error.